A Recursive Bayesian Approach for Identification of Network Configuration Changes in Distribution System State Estimation - Singh,R; Manitsas,E; Pal,BC; Strbac,G (IEEE Transactions on Power Systems, 2010)
This paper deals with the identification of network configuration changes in distribution system state estimation (DSSE). The models of critical network configurations are stored in the form of a model bank. A recursive Bayesian approach which utilizes the output of the state estimation function of each model in the bank is used to identify the correct configuration of the network. The concept is demonstrated on a part of the U.K. Generic Distribution System (UKGDS) model.